Development of environmentally conscious animal food supply to meet protein consumption in Blitar district - Azis, Rosidi; Juniarti Wulan Lestari; Hani Widhianata; Eunike Sri Puspaningsih; Eka Sudibya; Novan Noviansah; Triawati, Indri (Universitas Kristen Cipta Wacana, 2024)
Developing environmentally friendly livestock food provision in Blitar Regency through duck farming is one of the strategic efforts to increase community animal protein consumption while maintaining environmental sustainability. This community service program is designed with a participatory approach, education, and application of appropriate technology. The methods used include surveys, farmer training, implementation of technology to increase livestock productivity, use of biodigesters, and strengthening farmer institutions. The evaluation results showed a significant increase in farmer knowledge and skills, with an average post-test score increasing by 40% compared to the pre-test. The adoption of appropriate technology, such as feed biofermentation, and biodigesters, has succeeded in reducing production costs by 30%. Livestock productivity increased with production, while duck mortality rates decreased from 15% to 5%. Strengthening farmer institutions through the formation of farmer groups also increases the organizational capacity and bargaining power of farmers, including in accessing government financing and support. This program not only has a positive impact on farmer welfare but also contributes to meeting the community's animal protein needs and better environmental management. The sustainability of this program is expected to be achieved through supervision and synergy between the government, academics, and the private sector. This holistic approach shows great potential for replication in other areas with similar conditions.